ANALISIS PENGARUH E-MARKETING MIX DAN WORD OF MOUTH TERHADAP BUYING DECISION PADA 3 TOKO ONLINE POPULER DI KOTA PEKANBARU - Perdana, Riky; Restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2019)
This research is purposed for knowing the influence of E-Marketing Mixand Word of Mouth towards Buying Decision. While the benefits of this research is toanalyze the influence of E-Marketing Mix and Word of Mouth towards BuyingDecision on online shop users at Pekanbaru City. Data for the research are collectedwith questionaire which measured with Likert scale so te respondents has options tochoose which answers that suits each of them. Population on this research are onlineshop users who use among Lazada.co.id, Bukalapak.com, and Tokopedia.com andlive at Pekanbaru City where the population itself can not be estimated. As for thesample collection technique the researcher use the maximum likelihood techniquewith AMOS as an analysis for the structural equation and measurement model. Theresult of the research shows us that 1) E-Marketing Mix has a significantly positiveinfluence towards Buying Decision, 2) E-Marketing Mix has a significantly positiveinfluece towards Word of Mouth, 3) Word of Mouth has a significantly positive influece towards Buying Decision